1998
DOI: 10.1080/095008398178156
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical porosity in real quasicrystals

Abstract: The structure of real icosahedral quasicrystals of the Al± Pd± Mn system can be described in terms of a hierarchical self-similar packing of overlapping atomic clusters. An in¯ation scale factor ¿ 3 preserves long-range order but generates a hierarchy of holes and a fractal structure. Such holes have actually been observed and they might be of basic importance in the growth mechanism and stability of quasicrystals. § 1. IntroductionQuasicrystals are a form of the solid state which possesses a long-range transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 9 publications
3
19
0
Order By: Relevance
“…The residual broadening of the Bragg peaks may be ascribed to distortion fields around facetted dodecahedral voids as recently observed using contrast imaging and X-ray topography (Fig. 2) [17]; surfaces of the voids would then be coated or tapested by layers of approximants with increasing lattice parameters when going from the void border to the bulk around. Beyond the Bragg peak broadening, diffuse scattering has also been measured around the Bragg peaks, with average intensity increasing as Q 2 c and a 1/q 2 decay from the Bragg peak centre [28±30, 33].…”
Section: Phason Defects and Fluctuation In Real Quasicrystalssupporting
confidence: 56%
See 1 more Smart Citation
“…The residual broadening of the Bragg peaks may be ascribed to distortion fields around facetted dodecahedral voids as recently observed using contrast imaging and X-ray topography (Fig. 2) [17]; surfaces of the voids would then be coated or tapested by layers of approximants with increasing lattice parameters when going from the void border to the bulk around. Beyond the Bragg peak broadening, diffuse scattering has also been measured around the Bragg peaks, with average intensity increasing as Q 2 c and a 1/q 2 decay from the Bragg peak centre [28±30, 33].…”
Section: Phason Defects and Fluctuation In Real Quasicrystalssupporting
confidence: 56%
“…Models are easily built to demonstrate this [16]. Interestingly enough, phase contrast X-ray imaging techniques have been able to show facetted holes in single grain of the Al±Pd±Mn system [17,18] which, at least, suggests unusual growth defects (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the interpretation in reciprocal space (structure factor), an understanding of the real space fractal packing is also important. First of all, as pointed out by Coddens in an earlier debate on quasicrystals [337][338][339], the fractal in a dense 3-D material, if it ever exists, can only survive up to medium range, and the fractal correlation must break down over long range (otherwise the density of the material would vanish). Second, there should be a basic unit for the fractal packing, which defines the lower limit of the fractal length-scale.…”
Section: Mro: a Fractal Packing Propositionmentioning
confidence: 99%
“…Additional work by Beeli et al confirmed that pore size and spacing corresponded to diffusion models [4]. Two other hypotheses regarding the origin of porosity were based on quasicrystalline structural arguments [5,6]. The self-similar model proposes that porosity develops from specifically located vacancies that are inherent in the quasicrystal structure [5].…”
Section: Introductionmentioning
confidence: 97%
“…Two other hypotheses regarding the origin of porosity were based on quasicrystalline structural arguments [5,6]. The self-similar model proposes that porosity develops from specifically located vacancies that are inherent in the quasicrystal structure [5]. A modification of the selfsimilar model, the random covering theory, maintains the inherent and specifically located vacancies but increases the ability for deviation from the perfect arrangement by reducing the strict scaling laws [6].…”
Section: Introductionmentioning
confidence: 99%